HYBRID CULTURE IN KATOBA RITUAL OF MUNA (JOURNAL OF INDONESIAN ISLAM, 2024)
Initiation rituals for children in society, which combine ancient rituals and Islam, are an underexposed method for cultural selection. The research aims to address how the katoba tradition in the Muna community of Southeast Sulawesi results in cultural hybridization between customary practices and Islam. Interviews with traditional figures and ceremonial leaders, and observations of village and local katoba processions provided primary data. The research shows that the katoba processions effectively depict cultural hybridization as a result of how the community interprets the relationship between traditional customs and religion and how katoba undergoes cultural filtering, creating new forms and meanings. The cultural hybridization that occurs in katoba Muna is not only limited to material cultural components, but also in almost every sequence of rituals, from pre-ritual, procession, and even post-ritual stages; not only in dominant-subordinate power relations between adat (traditional customs) and Islam, but in equal relations. This research emphasises the dynamic relationship between customary practices and Islam, which involves constant exchange, reinterpretation, and substitution, assuring culture's continuous acceptance and meaning in society. This study also emphasises the necessity of studying rituals since cultural selection occurs in rituals.